Diurnal variations in seasonal precipitation in Iran from TRMM measurements. Issue 9 (1st November 2018) - Keikhosravi Kiany, Mohammad Sadegh; Balling, Robert C.; Cerveny, Randall S.; Krahenbuhl, Daniel S.
Abstract: We analyzed three-hourly TRMM precipitation data for Iran over the period 1998–2013. During the winter season when cyclonic storms dominate the precipitation, 66% of the country does not display a significant diurnal cycle in precipitation; however, the more mountainous portions of the country display a diurnal cycle with the time of maximum occurring near 12.50 LST. During the spring season when convective precipitation dominates, 55% of the country has a significant diurnal cycle in precipitation with a time of maximum near 15.50 LST; the result clearly shows the convective nature of the precipitation in this season. In summer season, only the northern and southern regions of the country receive much precipitation with most of it occurring between 15.50 and 18.50 LST, with the pattern being strongest in the southern areas. In fall season 42% of the country displays a significant diurnal cycle in precipitation. In this season, south regions of the country have their maximum precipitation frequency between 12.50 and 15.50 LST. Nearly identical patterns exist for precipitation amounts when compared to frequency.